2019
DOI: 10.1111/jfpe.13337
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of microwave vacuum drying of okra and the study of the product quality

Abstract: Microwave vacuum drying (MVD) was reported to be an efficient method to dehydrate vegetables. In this study, fresh okra was dehydrated by this technique. Orthogonal design was used to optimize the drying parameters (microwave power, vacuum level, and loading density) to achieve high drying rate and product quality. Microwave power (500, 700, and 900 W), vacuum level (45, 60, and 75 kPa) and loading density (3, 4, and 5 kg/m 2 ) were set up as the treatment factors. Drying rate, energy consumption, rehydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…The dried okra exhibited TPC in the range 932.07–1,871.61 mg GAE/100 g dried sample. The TPC of fresh okra in this study corresponded to the results on the investigation of TPC of fresh okra and was higher than tomato and green bean (76.9 and 35.5 mg GAE/100 g dried sample) (Xu et al, 2018). Denaturation of polyphenols was occurred during the heating process, inhibiting its activity by the increasing activity of polyphenol oxidase that was enhanced by the increasing temperature (Zhang et al, 2017).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The dried okra exhibited TPC in the range 932.07–1,871.61 mg GAE/100 g dried sample. The TPC of fresh okra in this study corresponded to the results on the investigation of TPC of fresh okra and was higher than tomato and green bean (76.9 and 35.5 mg GAE/100 g dried sample) (Xu et al, 2018). Denaturation of polyphenols was occurred during the heating process, inhibiting its activity by the increasing activity of polyphenol oxidase that was enhanced by the increasing temperature (Zhang et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…Thermal processing has the possibility to alter phytochemicals by affecting the integrity of the cell structure, resulting in component movement, which further caused leakage or disintegration by numerous chemical processes involving enzymes, light, and oxygen (Youssef & Mokhtar, 2014). However, prolonged use of the high temperature used during the drying process leads to the lower total phenol and flavonoid content in the product due to the decomposition of the phenolic acids and flavonoids by the long exposure to the heat (Xu et al, 2018; You et al, 2015), as shown by the results of okra drying using the microwave vacuum drying method. The phenomena of selective heating are related to microwave heating.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic models for degradation and formation of bioactive compounds were applied to relate and explain the changes in total anthocyanins, ascorbic acid, total phenols, total flavonoids, color parameters (Δ E ), HMF, enzymatic browning index, and antioxidant activities that occurred to the dried eggplant slices during drying under different drying processes (convective, infrared, ultrasonically assisted convective, freeze‐drying, and microwave drying processes). Zero, first, and second‐order kinetics models have been used to describe degradation reactions in foods and the Weibull model has been shown to fit the degradation of chemical compounds in strawberries and okra (Xu et al., 2020), sensory and ascorbic acid changes in melon (Amodio et al., 2013), and color changes in dried salak fruit (Ong et al., 2011). The cumulative distribution of the Weibull and combined distribution functions may be rewritten as follows (Amodio et al., 2013; Chouaibi, Mejri et al, 2019; Xu et al., 2020):CtC0=±ktzero - order kinetic model,CtC0=exp±ktzero - order kinetic model,tCt=±1kCnormale2+tCe,second - order kinetic model,CC0=k0C0k1k0C0k11exp±ktcombined kinetic model,CtC0=expkt...…”
Section: Methodsmentioning
confidence: 99%
“…Microwave vacuum drying also reduces the amount of heat required to evaporate water from food material compared to drying under atmospheric pressure (Nahimana & Zhang, 2011). Therefore, heat-sensitive food and agricultural products could be dried at relatively low temperatures due to the coupled effect of microwave and vacuum (Chauhan & Srivastava, 2009;Mousa & Farid, 2002;Xu et al, 2019).…”
mentioning
confidence: 99%